Gender, sex, and the city : Urdu Rekhtī poetry in India, 1780-1870 - Vanita, Ruth (Literatures and cultures of the Islamic world, 2012)
"This book explores the urban, cosmopolitan sensibilities of Urdu poetry written in the late eighteenth and early nineteenth centuries in Lucknow, which was the center of a flourishing Indo-Islamic culture. Ruth Vanita analyzes Rekhti, a type of Urdu poetry distinguished by a female speaker and a focus on women's lives, and shows how it became a catalyst for the transformation of the ghazal"--